Evaluation of Dam Effectiveness in Mitigating Flood Risk Due to Climate Change in Upstream Areas - Simanjuntak, Mangambit Juliandar (Universitas Syiah Kuala, 2025)
Global climate change has led to an increase in the intensity and frequency of extreme rainfall that contributes to increased flood risks, especially in upstream areas. In this context, dams play a crucial role as flood control infrastructure by regulating water flow and storing peak discharge. However, the effectiveness of dams in dealing with new hydrological challenges due to climate change has not been comprehensively evaluated, especially in upstream areas. This study aims to evaluate the effectiveness of dams in mitigating flood risks amid changing climate conditions, focusing on upstream areas. The method used is a systematic literature study of 10 selected scientific articles from 2018 to 2024, which were analyzed thematically and narratively. The results of the study show that dam effectiveness is greatly influenced by storage capacity, upstream environmental conditions, sedimentation, and the integration of adaptive technologies such as AI-based predictions and weather forecast-based reservoir management. Several studies emphasize the importance of adaptive management and land management to maintain optimal dam function. Thus, strengthening real-time monitoring systems, collaboration between institutions, and integration of climate data are the main recommendations for increasing dam resilience to future flood risks. This study contributes to the development of adaptive and sustainable water resource management policies in the era of climate change.